Intracardiac echocardiography improves lesion quality and ablation efficiency of pulmonary vein isolation in atrial fibrillation patients: a propensity score-matched analysis - Deng, Ye; Deng, Li; Gu, Qingqing; Chen, Qianwen; Zhang, Yang; Wei, Jun; Liu, Xu; Ji, Yuan; Sun, Ling; Wang, Qingjie (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPulmonary vein isolation (PVI) is a cornerstone of catheter ablation for atrial fibrillation (AF). Intracardiac echocardiography (ICE) offers real-time imaging that may enhance procedural outcomes compared to traditional x-ray guidance. This study evaluates the impact of ICE on PVI lesion quality and efficiency using a novel Ablation Index Functional Validation (AIFV) system.MethodsThis single-center, retrospective, matched cohort study included AF patients undergoing catheter ablation between June 2022 and June 2023 at The Third Affiliated Hospital of Nanjing Medical University. Patients were grouped based on ICE use (ICE vs. No-ICE), with intraoperative data recorded via the VisiTag system and analyzed by AIFV. Propensity score matching (1:1) was applied to compare procedural efficiency and lesion quality (primary endpoints) and AF recurrence (secondary endpoint) between groups.ResultsOf 126 patients enrolled (61 ICE, 65 No-ICE), 46 matched pairs were analyzed. PVI was achieved in all cases without severe complications. The ICE group demonstrated significantly shorter total PVI time [2,819 s (2,565 s, 2,953 s) vs. 3,153 s (2,696 s, 3,831 s), p = 0.006], higher radiofrequency (RF) time ratio (59.1% ± 13.9% vs. 48.2% ± 11.6%, p < 0.001), and higher effective ablation-index (AI) ratio (96.1% ± 4.5% vs. 91.2% ± 3.9%, p < 0.001) compared to the No-ICE group. Left and right PVI times were also reduced (p = 0.034 and p = 0.029, respectively). At 12-month follow-up, AF recurrence rates were significantly lower in the ICE group (7.7% vs. 30.8%, p = 0.038) in persistent AF patients.ConclusionICE enhances the quality of lesions and the ablation efficiency of PVI in AF patients, as shown by the AIFV system.